Varieties of populism in Europe in times of crises - Caiani, Manuela 1976-; Graziano, Paolo 1971- (Routledge, 2021)
Populism is booming across all the nuances of the political spectrum. It occupies relevant positions in national parliaments, in governmental coalitions with mainstream parties or as successful challengers of the political status quo. This volume sheds new light on the topic from different methodological and theoretical angles and offers evidence from a variety of cases on the ‘why’ and ‘how’ questions on populism’s emergence and consolidation in Europe over the past 30 years. The volume, composed of eight chapters, investigates how different populist parties in the European Union have been affected by the various crises, disentangling the role of the Great Recession vis-à-vis other factors (such as political and party system factors, but also structural social changes or cultural opportunities) in the growing strength of populist parties in various European countries [...].
The chapters in this book were originally published as a special issue of "West European Politics", volume 42 (2019), issue 6
Keywords: Populismus; Europa; Populism / Europe; Crises / Political aspects / Europe